An update review of the application of single-cell RNA sequencing in pregnancy-related diseases - Zhou, Zhiyi; Yang, Xiuhua (Frontiers in Endocrinology, 2024)
Reproductive success hinges on the presence of a robust and functional placenta. Examining the placenta provides insight about the progression of pregnancy and valuable information about the normal developmental trajectory of the fetus. The current limitations of using bulk RNA-sequencing (RNA-seq) analysis stem from the diverse composition of the placenta, hindering a comprehensive description of how distinct trophoblast cell expression patterns contribute to the establishment and sustenance of a successful pregnancy. At present, the transcriptional landscape of intricate tissues increasingly relies on single-cell RNA sequencing (scRNA-seq). A few investigations have utilized scRNA-seq technology to examine the codes governing transcriptome regulation in cells at the maternal-fetal interface. In this review, we explore the fundamental principles of scRNA-seq technology, offering the latest overview of human placental studies utilizing this method across various gestational weeks in both normal pregnancies and pregnancy-related diseases, including recurrent pregnancy loss (RPL), preeclampsia (PE), preterm birth, and gestational diabetes mellitus (GDM). Furthermore, we discuss the limitations and future perspectives of scRNA-seq technology within the realm of reproduction. It seems that scRNA-seq stands out as one of the crucial tools for studying the etiology of pregnancy complications. The future direction of scRNA-seq applications may involve devolving into functional biology, with a primary focus on understanding variations in transcriptional activity among highly specific cell populations. Our goal is to provide obstetricians with an updated understanding of scRNA-seq technology related to pregnancy complications, providing comprehensive understandings to aid in the diagnosis and treatment of these conditions, ultimately improving maternal and fetal prognosis.